Experimental minimum threshold for Phytophthora cinnamomi root disease expression on Quercus suber - María Socorro SERRANO; Pedro RÍOS; Mario GONZÁLEZ; María Esperanza SÁNCHEZ (Phytopathologia Mediterranea, 2015)
Quercus suber seedlings were potted in soils infested with increasing concentrations of Phytophthora cinnamomi chlamydospores and submitted to weekly flooding for 3 months to favour root infections. Increasing quantities of chlamydospores led to an exponential increase in their ability to germinate. Root symptoms (necrosis and/or absence of feeder roots) were significantly more severe than those recorded in uninfested soil only for plants potted in soils infested with 61 cfu g-1 or more. Although generated using potting mix, this minimum threshold represents a tool for checking the potential infectivity of infested soils or to assess the effectiveness of some control methods to reduce soil inoculum. However, a low level of root infection was recorded even at 3 cfu g-1. Therefore, long-term disease risk may be present whenever the pathogen is detectable in oak forest soils.